The Work and the Evolution of Earnings - Subačienė, Rasa (Ekonomika, 1998)
This article investigates connection between work and earnings, development of pay’s forms and systems. The work was found, when people learned, how to adapt to nature and began it’s elements aim at their purposes. When division of labor and reason to change one thing to another were found, turned up the problem of earnings. There are adduced earning dependance upon such factors as content of labour, social conditions, varous social and other groups view to the labour, development of industries’ relations. Production mode, grounded on hired labour, reveals two forms of earnings: piece wage and pay by the time. There were instilled various pay by the time and piece wage modifications by variaty of two public production subdivision and stability of capital composition. On 8th and 9th decade spread the sphere of pay by the month and get narrow part in earnings of payment by the piece, there are found various systems of premium in Lithuania, too.